The strength of the strong - London, Jack (Grosset & Dunlap, 1914)
Jack London was one of the most prolific American writers of the early 20th century, and remains one of the most beloved, but while his novels have remained continuously in print for a century, his short stories have been much harder to find. This varied and eclectic collection shows many of his concerns and interests: the lives of the indigenous people of America, man's struggle agaianst nature, his sympathy and compassion for the poor, and his predilection for writing stories set in a dystopian future. -- Publisher's description.
The strength of the strong.--South of the slot.--The unparalleled invasion.--The enemy of all the world.--The dream of Debs.--The sea-farmer.--Samuel.
Jack London was one of the most prolific American writers of the early 20th century, and remains one of the most beloved, but while his novels have remained continuously in print for a century, his short stories have been much harder to find. This varied and eclectic collection shows many of his concerns and interests: the lives of the indigenous people of America, man's struggle agaianst nature, his sympathy and compassion for the poor, and his predilection for writing stories set in a dystopian future. -- Publisher's description.
Keywords: Nouvelles. / rvmgf; Short stories / lcgft; Short stories / fast / (OCoLC)fst01726740; short stories. / aat